Performa Pertumbuhan Tiga Varietas Ayam Kedu Umur 0–10 Minggu - Akramullah, Muh; Kurnianto, Edy; Lestari, Dela Ayu; Setiatin, Enny Tantini; Setiaji, Asep (Universitas Bengkulu, 2025)
This study aimed to evaluate the growth performance of Red-Combed Kedu (RCK), Black-Combed Kedu (BCK), and White Kedu (WK) chickens based on sex during the early growth phase (0 to 10 weeks of age). A total of 136 Kedu chickens were raised under uniform management conditions, consisting of 99 RCK (65 roosters and 34 hens), 29 BCK (5 roosters and 24 hens), and 8 WK (6 roosters and two hens). Body weight was recorded weekly and analysed using a two-way General Linear Model (GLM) in SAS to assess the effects of chicken variety, sex, and their interaction. The Shapiro–Wilk test confirmed that the data were normally distributed (p > 0.05). The results showed that sex had a significant effect on body weight from weeks 3 to 10 (p < 0.05), with roosters consistently exhibiting higher weights than hens. Significant differences among chicken varieties were observed only in the hen group at weeks 9 and 10, where BCK hens had higher body weights (p < 0.05) than WK hens, while RCK hens showed intermediate values. In contrast, no significant differences were found among rooster groups at any age. These findings suggest that genetic factors play an essential role in influencing growth performance in Kedu chickens, particularly in hens. This information provides a valuable foundation for breeding selection and the conservation of local chicken genetic resources.